Association between cardiac metabolic index and diabetic kidney disease: a cross-sectional study of NHANES 1999–2018 - Lu Zhang; Cuiying Liang; Zhaoqi Yan; Qingzhen Li (Journal of Health, Population and Nutrition)
Abstract Background The Cardiac Metabolic Index (CMI) is a comprehensive metabolic indicator, but studies on its relationship with Diabetic Kidney Disease (DKD) are limited. We aim to explore the association between CMI and DKD. Methods We obtained participant-related data from the National Health and Nutrition Examination Survey (NHANES), including complete information on DKD, CMI, and other covariates. We employed weighted multivariable logistic regression models, restricted cubic spline (RCS) regression analysis, subgroup analyses, and interaction tests to explore the relationship between CMI and DKD. Additionally, we utilized receiver operating characteristic (ROC) curves to compare the performance of CMI in identifying DKD relative to a body shape index (ABSI), body roundness index (BRI), visceral adiposity index (VAI), and lipid accumulation product (LAP) indices. Results According to the logistic regression analysis, a positive correlation between CMI and DKD was observed among the 2371 participants included in the study (OR: 1.40, 95% CI: 1.19–1.66). RCS analysis indicated that this relationship is nonlinear. When CMI was converted from a continuous variable to quartiles, the prevalence of DKD in the highest quartile group showed a significant 84% increase compared to the lowest quartile group (OR: 1.84, 95% CI: 1.24–2.72). The area under the ROC curve of CMI for identifying DKD was 0.67, outperforming other indices. The results of subgroup analyses and interaction tests were stable. Conclusion Elevated CMI is associated with an increased risk of DKD and can serve as a low-cost screening tool, allowing physicians to potentially identify high-risk diabetic patients early and implement timely interventions to slow the progression of DKD.